ANALISIS GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN PADA PT SANFREMY PRATAMA MEDAN - RAHEL JUNITA (LP2MTBM MAKARIOZ, 2022)
PT Sanfremy Pratama Medan in the period 2015-2022, where the increase in CSR costs and environmental costs is not in line with PT Sanfremy Pratama's ability to prevent risks caused by environmental damage to the community, which has an impact on the company's ability to increase profits or increase asset returns, thus hampering PT Sanfremy Pratama's productivity. This study aims to determine whether CSR costs and environmental costs, either partially, or simultaneously have a significant effect on the return on assets of PT Sanfremy Pratama Medan. Data analysis in this study uses descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests, where the population in this study is the quarterly financial statements of PT Sanfremy Pratama Medan in 2015-2022, while the sampling method in this study uses purposive sampling. The results of this study stated that simultaneously CSR costs and environmental costs had a significant effect on the return on assets of PT Sanfremy Pratama Medan, while partially only variable environmental costs had a significant effect on the return on assets of PT Sanfremy Pratama Medan